A Positioning Method Based on Train Motion Model and Inertial Gyroscope - LIANG Fei (Kongzhi Yu Xinxi Jishu)
GPS/BD positioning is one of the main solution of train positioning. In order to solve the problem of satellite signal loss,this paper proposed a train positioning method in satellite signal bind zone based on the train motion model and the inertial gyroscope, and a Kalman filter to optimize the processing. The simulation results show that the proposed method can improve the positioning accuracy when the satellite signal is available,and the positioning results with higher accuracy can be obtained in a certain time when the satellite signal is lost.